C1 Complex: An Adaptable Proteolytic Module for Complement and Non-Complement Functions - Lu, Jinhua; Kishore, Uday (Frontiers in Immunology, 2017)
Complement C1 is the defining component of the classical pathway. Within the C1qC1r2C1s2 complex, C1q functions as a molecular scaffold for C1r2C1s2 and C1q binding to its ligands activates these two serine proteases. The classic C1q ligands are antigen-bound antibodies and activated C1s cleaves C4 and C2 to initiate the complement cascade. Recent studies suggest broad C1 functions beyond the complement system. C1q binds to the Frizzled receptors to activate C1s which cleaves LRP6 to trigger aging-associated Wnt receptor signalling. C1q binds to apoptotic cells and the activated C1 proteases cleave nuclear antigens. C1s also cleaves MHC class I molecule and potentially numerous other proteins. The diversity of C1q ligands and C1 protease substrates renders C1 complex versatile and modular so that it can adapt to multiple molecular and cellular processes besides the complement system.